Type 1 Innate Lymphoid Cell Biology: Lessons Learnt from Natural Killer Cells - Jiao, Yuhao; Huntington, Nicholas D.; Belz, Gabrielle T.; Seillet, Cyril (Frontiers in Immunology, 2016)
Group 1 innate lymphoid cells (ILC) comprise the natural killer (NK) cells and ILC1 which reside within peripheral tissues. Several different ILC1 subsets have recently been characterised, however no unique markers to define these subsets have been identified. Whether ILC1 and NK cells are in fact distinct lineages, or alternately exhibit transitional molecular programs, that allow them to adapt to different tissue niches remains an open question. NK cells are the prototypic member of the Group 1 ILC and have been historically assigned the functions of what now appears to be a multi-subset family that are distributed throughout the body. This raises the question of whether each of these populations mediate distinct functions during infection and tumour immunosurveillance. Here, we review the diversity in the Group 1 ILC subsets with regards to their transcriptional regulation, localization, mobility and receptor expression and highlight the challenges in unraveling the individual functions of these different populations of cells.